POLA DAN PEMERINTAH DALAM PENCEGAHAN TRAFFICKING IN PERSONS DI LOMBOK TIMUR - Nunung Rahmania; Atika Zahra Nirmala; Zahratul'ain Taufik; Aryadi Almau Dudy; Suheflihusnaini Ashady (Faculty of Law, Maranatha Christian University, 2023)
Human Trafficking is an iceberg phenomenon that is growing all over the world including in Indonesia. Indonesia is a tier 2 surveillance country because human trafficking cases are still high and one of the regions contributing to human trafficking cases is East Lombok Regency, West Nusa Tenggara. The purpose of this study is to analyze and find out how pattern of human trafficking in East Lombok and the role of the East Lombok Regency government in preventing human trafficking. The results showed that first, pattern human trafficking in East Lombok Regency which starts from the recruitment process carried out by neighbors, family, friends, and people who first go abroad, document forgery and manipulation of victims' data are made outside the East Lombok Regency area, and the departure process is relay and departure is not from East Lombok Regency but from the area where the documents are made. Second, the role of the East Lombok Regency Government for prevent human trafficking by conducting scheduled socialization in villages/villages that are vulnerable to human trafficking victims, forming Productive Migrant Villages, and providing training to retired migrant workers/families by forming novice business heroes. However, the Government's efforts to prevent human trafficking have not been maximized and effective due to the lack of coordination between related institutions and public awareness of the dangers of trafficking in persons.